2010
DOI: 10.2337/dc09-2007
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Foot Ulceration and Amputation Risk in a Multiracial Cohort of Diabetic Patients on Dialysis Therapy

Abstract: OBJECTIVETo evaluate the prevalence of lower-limb complications in a multiracial cohort of patients with diabetes receiving dialysis.RESEARCH DESIGN AND METHODSThis work was a cross-sectional study of lower-limb complications in dialysis-treated patients with diabetes in the U.K. and U.S.RESULTSWe studied 466 patients (139 U.K.; 327 U.S.). The prevalence of lower-limb complications was high (foot ulcers 12%, neuropathy 79%, peripheral arterial disease 57%, history of foot ulceration 34%, and prior amputation 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 12 publications
11
77
2
Order By: Relevance
“…As far as we know this is the first study on linking LLA amongst Australian aborigines with ESRF. This association has previously been identified however only in patient with DM amongst ethnic minorities but not in patients with ESRF on 27 Similarly, patients from an African American background have also been found to be at five-times higher risk of diabetic LLA, this has primarily been attributed to lifestyle factors and genetic makeup. 28 At the same time, Canadian aboriginal peoples have been found to have high rates of foot complications that places them at high risk of ulceration at a younger age, 29 studies have found aboriginal subjects to be younger than non-aboriginal counterparts at the time of diabetes diagnosis as well as first major LLA.…”
Section: Discussionmentioning
confidence: 77%
“…As far as we know this is the first study on linking LLA amongst Australian aborigines with ESRF. This association has previously been identified however only in patient with DM amongst ethnic minorities but not in patients with ESRF on 27 Similarly, patients from an African American background have also been found to be at five-times higher risk of diabetic LLA, this has primarily been attributed to lifestyle factors and genetic makeup. 28 At the same time, Canadian aboriginal peoples have been found to have high rates of foot complications that places them at high risk of ulceration at a younger age, 29 studies have found aboriginal subjects to be younger than non-aboriginal counterparts at the time of diabetes diagnosis as well as first major LLA.…”
Section: Discussionmentioning
confidence: 77%
“…44 Additionally, the high risk of foot ulceration among patients with diabetes mellitus who receive dialysis has been confirmed in a number of studies. [45][46][47] A temporal association between the start of dialysis and an increased risk of foot ulcer ation has been reported. 45 Moreover, in another series of studies, undergoing dialysis was found to be an inde pendent risk factor for foot ulceration in patients with diabetes mellitus and the protection against foot ulcers seen in some ethnic populations is lost in patients receiving dialysis.…”
Section: Microvascular Complicationsmentioning
confidence: 97%
“…In subsequent collaborative studies between the United Kingdom and the United States, dialysis has been shown to be an independent risk factor for foot ulceration in diabetic patients, 34 and the same group also confirmed that the ethnic protection from neuropathy and risk of foot ulcer is lost when diabetic patients of Asian origin are on longterm dialysis therapy. 35 Of note, even nondiabetic patients in dialysis units have observed the high risk of foot ulcers and amputations in the dialysis unit: Carey wrote "throughout dialysis, patients suddenly appear with amputations: very often with heavily managed feet rapidly followed by crutches and then wheelchairs." 36 Thus diabetic patients on dialysis must be regarded as being at extremely high risk of lower extremity complications, and warrant regular foot-care education and podiatry.…”
Section: History Of Foot Ulceration or Amputationmentioning
confidence: 99%